Pengaruh Lama Pengomposan dan Variasi Jumlah Cacing (Eudrillus eugenie) Selama Proses Vermikomposting Pada Limbah Blotong Tebu (Saccharum officinarum L.) - Siti Rahmawati Wahyuningsih; Saimul Laili; Hasan Zayadi (Jurnal Ilmiah Biosaintropis (Bioscience-Tropic), 2023)
Filter mud is one of the dense waste produced by sugar factories. So far, sugar factories dispose the filter mud by directly piling them up in the field without going through any recycle process, causing serious problems for the sugar factory and the surrounding environment. Filter mud has the potential to be made as organic fertilizer. Besides being a adequately complete nutrient source, it can also help fixing the soil physical, chemical and biological properties. Vermicompost is an eco friendly organic fertilizer and has its own advantages compared to other compost which we have known so far. This study aims to determine the macro nutrient elements, namely C-Organic, N-Total and C/N Ratio in sugar filter mud which are composted by the vermicomposting method using earthworm species (Eudrilus eugeniae). The method used is the preservation of worms with bedding and food material from filter mud waste for 28 days, the C-organic test with spectrophotometry and the N-total test using Kjeldahl-Nessier method. The calculation of the C/N ratio is the value comparison of C-organic and N-total. Data analysis is using Anova with the help of Jamovi and also by doing a further test of BNJ 5%. The best results of the study are of C-organic levels obtained on day 14, for N-total during the vermicomposting process, the value of N-total always increases during composting and the best C/N ratio is obtained on the 14th day observations with control treatment M1 (without worms), M1 (25 worms) and M2 (with 50 worms). Anova test and 5% BNJ showed that the results of the observation day variable had a significant effect with the quality of macro elements in vermicompost, while the differences in control treatment had no effect on the quality of micro nutrients.